The Guarantee Fund of Investment as an Element of Protection Infrastructure of the Securities Market - Vasiliev, Oleksiy; Nimkovych, Andrij (Social Economics, 2019)
The article provides a theoretical justification of necessity to create an investment guarantee fund for the Ukrainian securities market. In the article the foreign experience of the functioning of similar funds, their principles and peculiarities of the organization were emphasized. In particular, the funds of Estonia and Lithuania were analyzed. The purpose of such Guarantee Funds is to provide protection for investors through an investment organization, in case of failure of the investment organization. In order to achieve these goals, the Funds accumulate invest funds of financial resources in government securities and securities of central banks, and in the course of an insurance event, they pay insurance premiums in due time. In the article, it is noted that the object of investors protection is not investment risk, it means, the probability of loss because the investment will not bring profit or loss of value. The models of Estonia and Lithuania show a universal institution that reflects the protection of the clients’ interests of credit institutions (or depositors), clients of investment organizations (or investors), owners of mandatory pension funds shares and insurers who have entered into pension contracts with insurers. Based on the study of model and features in other countries, the authors proposed prototype of structure of a similar institution in Ukraine – «Fund for the Guarantee of Individual Deposits and Investments». One of the main bases is anticipated that such an institution should have a higher reimbursement rate for participants, the functionality and consistency of work with funds of accumulated financial resources will be analogous to foreign models. The management of the Fund will be formed by delegating to it representatives of various government agencies and self-regulatory organizations that will ensure real transparency and objective decision-making of the Fund.